Theoretical Review of Experiments (Poging) in the Criminal Code - Pardamean Harahap; Suparji Ahmad (Journal of Social Research, 2023)
Probation Institute regulated in the Criminal Code called poging according to doctrine is a crime that has been started, but has not been completed or is not perfect, the Criminal Code can threaten an act in order to prevent the occurrence of victims. The Problem Formulation is: How is the Criminal Law Review related to Experiments (poging) in Indonesia?, while the Research Method used is Normative Research, which is obtained from documents or library materials. The objective probation theory that the basis for the conviction of probation is because the act has endangered a legal interest, and the subjective theory of probation that the basis for the conviction of probation is the harmful nature of the perpetrator.